Government Cash Management : Its Interaction with Other Financial Policies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This technical note describes the interaction of government cash management with other financial policies. The note offers guidance on policy, institutional, and practical issues for governments looking to develop a more sophisticated cash management function, specifically to move toward more active cash management. This involves financial market intervention by the government cash manager, with the aim of smoothing the projected short-term profile of the government's net cash balances. The note is particularly relevant to emerging market countries where there are already functioning, if not necessarily well-developed, domestic money and bond markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet